Interview with Michael Finseth: Performance in the TV Show Mil oficios - Delgado Del Aguila, Jesús Miguel (2025)
In this interview, Michael Finseth uses his experiences to tell how he came to be introduced to the world of acting; especially, in the series Mil oficios (2001-2003). On this occasion, the Peruvian actor is very detailed when recalling some anecdotes with the casting, recording and related work process that he did when starring as the character Memo, such as participating in circuses and nationwide tours with the entire cast of the series. All this intense work would only reveal that the program itself captivated the audience at that time, so much so that some typical phrases of the characters and some characterizations remained in memory. Likewise, it is interesting how Finseth is grateful for the learning he received from all the actors who collaborated there and how he explains the evolution of the character he starred in, who would be distinguished by having multiple nuances: comic, romantic, serious, witty, etc. In short, this conversation is transcendental because it is possible to know what the actor’s experiences were and how it was possible to establish in Peru a prototype of a comedy soap opera that to this day remains in many of the country’s television programs.